Grain boundary diffusion material, neodymium iron boron magnet and its manufacturing method, and application
The grain boundary diffusion process with controlled compositions enhances coercive force and thermal stability in neodymium iron boron magnets, addressing the limitations of conventional methods and achieving high-performance magnets.
Patent Information
- Application Number
- JP2023544212
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-08-27
- Filing Date
- 2022-01-17
- Publication Date
- 2024-12-16
- Estimated Expiration
- 2042-01-17
AI Technical Summary
Existing neodymium iron boron magnets suffer from low coercive force and poor thermal stability, limiting their use in high-temperature applications, and conventional grain boundary diffusion methods fail to fully utilize heavy rare earth elements for enhancing coercive force.
A grain boundary diffusion material for neodymium iron boron magnets comprising specific compositions and processes, including a diffusion substrate with controlled light rare earth, copper, and optionally other elements, followed by a heat treatment to form a Cu-rich phase at grain boundaries, enhancing coercive force and residual magnetic flux density.
The method significantly improves coercive force and maintains residual magnetic flux density, enabling high-performance magnets suitable for demanding applications like 54SH brand products.
Smart Images

Figure 0007600415000006 
Figure 0007600415000007 
Figure 0007600415000008
Abstract
Description
[Technical field]
[0001] The present invention relates to a grain boundary diffusion material, a neodymium iron boron magnet, a manufacturing method thereof, and applications thereof. [Background technology]
[0002] Sintered N-Fe-B magnets have excellent magnetic energy density and are widely used in wind power generation, electronic communications, new energy vehicles and other fields, but due to their low coercivity and poor thermal stability, they will exhibit thermal demagnetization during high temperature operation, limiting their application in high temperature fields. How to increase the coercivity and thermal stability of magnets has attracted the attention of more and more scholars.
[0003] The China Rare Earth Journal reports that the grain boundary diffusion of Tb in sintered NdFeB magnets 70 Cu 30 Thermal stability and microstructure studies of the alloy (Zhou Toujun et al., Jiangxi Provincial Key Laboratory of Rare Earth Magnetic Performance Materials and Devices, 2021.01.21) have been reported. Commercially available sintered magnets (PrNd) 29.25 Dy 1.62 Fe bal B 0.98 Co 0.83 M 0.59 (Mass fraction wt.%, M = Nb, Al, Cu, Zr, Ga) was used to obtain a magnet material with a significantly improved coercive force and almost no change in residual magnetic flux density by using a specific grain boundary diffusion source and diffusion temperature. This diffusion method significantly increases the neodymium-rich phase and makes it more continuous and clearly distributed. At the same time, (Nd,Tb)2Fe 14The B core-shell structure is formed to encase the crystal grains, enhancing the demagnetization coupling between adjacent crystal grains and improving the coercivity of the magnet. Specifically, the coercivity increases by 15.4%, from 17.37 kOe to 20.04 kOe. At the same time, the temperature coefficient of coercivity and the temperature coefficient of remanence both decrease obviously, and within the temperature range of 20 to 200°C, the absolute value of the temperature coefficient of coercivity decreases from 0.454% / °C to 0.442% / °C, and the temperature coefficient of remanence decreases from 0.124% / °C to 0.12% / °C. However, the magnet material of the document also has the disadvantage that the increase in coercivity due to diffusion is limited, being only 2.67 kOe.
[0004] In the conventional production of NdFeB, the addition of a small amount of Cu has a great effect on increasing the coercive force. In the case of diffusion products, if the amount of Cu added in the diffusion matrix exceeds 0.5wt%, the grain boundary diffusion will greatly reduce the effect of improving the coercive force of the product, and at the same time, the residual magnetic flux density will also be reduced. In the general compounding design, the Cu in the diffusion matrix is directly set to be greater than 0.5wt.%, and the purpose of high Cu content is further achieved by diffusing Tb to produce high-performance 54SH brand products. However, in reality, if the amount of Cu added is greater than 0.5wt.%, it is difficult for the magnetic performance after Tb diffusion to meet the requirements of the 54SH brand.
[0005] Currently, there is a lack of manufacturing processes that can fully utilize the coercivity-improving effect of heavy rare earth elements. Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention provides a grain boundary diffusion material, a NdFeB magnet, its manufacturing method and application, mainly to solve the defect of the prior art that the coercive force is not improved by adding heavy rare earth elements in the grain boundary diffusion process. The NdFeB magnet manufactured by the grain boundary diffusion material of the present invention can improve the coercive force more significantly and maintain the remanence almost constant under the premise of adding the same amount of heavy rare earth elements. [Means for solving the problem]
[0007] The present invention mainly solves the above technical problems through the following technical solutions.
[0008] The present invention provides a grain boundary diffusion material for a neodymium iron boron magnet, comprising a diffusion substrate and a diffusion source, which is a raw material to be diffused and is added during grain boundary diffusion treatment; The diffusion matrix comprises the following components: LR: 29 to 30 wt.%, the LR being a light rare earth element; Cu: 0.15-0.5wt.%, B: 0.99-1.05 wt.%, Fe: 67-70 wt.%, where wt.% is the percentage of the mass of each component with respect to the total mass of the neodymium iron boron magnet, the diffusion source includes Cu and Tb; The percentage of the mass of Cu in the neodymium iron boron magnet relative to the total mass of the neodymium iron boron magnet is greater than 0.5 wt.%.
[0009] In the present invention, as known to those skilled in the art, the diffusion substrate generally means a magnet material that can be directly subjected to grain boundary diffusion treatment, and may generally be a sintered body.
[0010] In the present invention, the LR content in the diffusion matrix is preferably 29.4 to 30 wt.%, for example, 29.42 wt.%, 29.5 wt.%, 29.62 wt.%, 29.65 wt.%, 29.6 wt.%, 29.68 wt.%, 29.7 wt.% or 29.73 wt.%, where wt.% is the percentage in the total mass of the neodymium iron boron magnet.
[0011] In the present invention, the LR may be conventional in the art and may generally include one or more of Nd, Pr and PrNd alloys, preferably Nd, "Nd and Pr" or PrNd alloys.
[0012] When the LR is Nd, the content of the Nd is preferably 29.4-29.8wt%, for example, 29.42wt%, 29.5wt%, 29.6wt%, 29.68wt%, 29.7wt%, or 29.73wt%, where wt% is the percentage in the total mass of the NdFeB magnet. When the LR is Nd, the residual magnetic flux density is higher than that of the Nd and Pr, and the PrNd alloy NdFeB magnet material.
[0013] When the LR is Nd and Pr, the Nd content is preferably 21 to 23 wt.%, for example, 22.28 wt.%, and the Pr content is preferably 6 to 8 wt.%, for example, 7.43 wt.%, where wt.% is the percentage in the total mass of the neodymium iron boron magnet.
[0014] When the LR is a PrNd alloy, the content of the PrNd alloy is preferably 29 to 30 wt.%, where wt.% is the percentage in the total mass of the neodymium iron boron magnet, and in the PrNd alloy, the mass ratio of Nd to Pr is, for example, 3:1.
[0015] In the present invention, the Cu content in the diffusion matrix is preferably 0.15 to 0.35 wt.%, for example, 0.16 wt.%, 0.24 wt.%, 0.25 wt.% or 0.34 wt.%, where wt.% is the percentage of the total mass of the NdFeB magnet.
[0016] In the present invention, the B content is preferably 0.99 to 1.03 wt.%, for example 0.99 wt.%, 1 wt.%, or 1.01 wt.%, where wt.% is the percentage in the total mass of the neodymium iron boron magnet.
[0017] In the present invention, the diffusion matrix may further contain additive elements common in the art, such as one or more of Al, Co, Ti and Tb.
[0018] Here, when the diffusion matrix contains Al, the Al content may be 0.2 to 0.4 wt.%, for example 0.3 wt.%, where wt.% is the percentage in the total mass of the NdFeB magnet.
[0019] Here, when the diffusion matrix contains Co, the Co content may be 0.5 to 1.5 wt.%, for example 1 wt.%, where wt.% is the percentage of the total mass of the NdFeB magnet.
[0020] Here, when the diffusion matrix contains Ti, the Ti content may be 0.1 to 0.2 wt.%, for example 0.15 wt.%, where wt.% is the percentage in the total mass of the neodymium iron boron magnet.
[0021] Here, when the diffusion matrix contains Tb, the content of Tb is preferably 1 wt.% or less, for example, 0.8 wt.%, where wt.% is the percentage in the total mass of the NdFeB magnet.
[0022] In the present invention, the inventors further discovered that when the diffusion matrix does not contain Al and Co, the coercivity of the NdFeB magnet obtained by the grain boundary diffusion treatment can be improved more significantly.
[0023] As known to those skilled in the art, when the diffusion matrix does not contain Al, it generally means that no additional Al is added during the preparation of the diffusion matrix, but Al is inevitably introduced in an amount of 1 wt.% or less, for example, 0.06 wt.% or 0.07 wt.%, during the preparation of the diffusion matrix, where wt.% is the ratio of Al to the total mass of the NdFeB magnet.
[0024] In the present invention, the Fe content in the diffusion matrix is preferably 67 to 69 wt.%, for example, 66.87 wt.%, 67.12 wt.%, 67.57 wt.%, 67.6 wt.%, 67.69 wt.%, 67.76 wt.%, 67.9 wt.%, 67.91 wt.% or 68.03 wt.%, where wt.% is the ratio to the total mass of the NdFeB magnet.
[0025] In the present invention, the content of Tb in the diffusion source may be that which is common in this field, and is preferably 0.1-1.5 wt.%, for example, 0.65 wt.%, 0.66 wt.%, 0.7 wt.%, 0.81 wt.%, 0.85 wt.%, 0.86 wt.%, 0.88 wt.% or 1 wt.%, where wt.% means the ratio of the content of Tb to the total mass of the NdFeB magnet.
[0026] In the present invention, the Cu content in the neodymium iron boron magnet is preferably 0.51 to 0.65 wt.%, for example, 0.51 wt.%, 0.52 wt.%, 0.55 wt.%, 0.61 wt.%, 0.62 wt.%, 0.63 wt.% or 0.65 wt.%, where wt.% means the ratio of the Cu content to the total mass of the neodymium iron boron magnet.
[0027] In the present invention, the manufacturing method of the diffusion substrate can be a method commonly used in the art, and generally includes the steps of melting, smelting, crushing, molding and sintering the raw material composition of the diffusion substrate in sequence.
[0028] Here, the temperature of the smelting is preferably 1400-1550° C., for example, 1480° C., 1500° C. or 1520° C. As known to those skilled in the art, the temperature of the smelting has an error of ±20° C. during actual operation.
[0029] Here, the thickness of the alloy sheet obtained after the melting and smelting is preferably 0.25-0.55 mm, for example, 0.3 mm. As known to those skilled in the art, the thickness of the alloy sheet has an error of ±0.05 mm in practical operation.
[0030] Here, the pulverization is generally carried out in the order of hydro-pulverization and jet mill pulverization.
[0031] The particle size of the powder obtained after the pulverization is, for example, 3 to 5 μm.
[0032] Here, the molding is generally magnetic field molding, and the magnetic field strength of the magnetic performance molding is, for example, 1.6 T or more.
[0033] Here, the sintering temperature is, for example, 1000 to 1100°C.
[0034] Here, the sintering time is, for example, 4 to 6 hours.
[0035] In one specific embodiment of the present invention, the diffusion matrix is composed of 29.6 wt.% Nd, 0.24 wt.% Cu, 0.15 wt.% Ti, 1 wt.% B, 0.06 wt.% Al and 67.69 wt.% Fe, where wt.% is the percentage of the mass of each component relative to the total mass of the NdFeB magnet, and the diffusion source is 0.88 wt.% Tb and 0.38 wt.% Cu.
[0036] In one specific embodiment of the present invention, the diffusion matrix is composed of 29.68 wt.% Nd, 0.16 wt.% Cu, 0.15 wt.% Ti, 1 wt.% B, 0.06 wt.% Al and 67.6 wt.% Fe, where wt.% is the mass percentage of each component relative to the total mass of the NdFeB magnet, and the diffusion source is 0.86 wt.% Tb and 0.49 wt.% Cu.
[0037] In one specific embodiment of the present invention, the diffusion matrix is composed of 29.73 wt.% Nd, 0.34 wt.% Cu, 0.15 wt.% Ti, 1 wt.% B, 0.07 wt.% Al and 67.57 wt.% Fe, where wt.% is the mass percentage of each component relative to the total mass of the NdFeB magnet, and the diffusion source is 0.85 wt.% Tb and 0.29 wt.% Cu.
[0038] In one specific embodiment of the present invention, the diffusion matrix is composed of 29.7 wt.% Nd, 0.5 wt.% Cu, 0.15 wt.% Ti, 1 wt.% B, 0.06 wt.% Al and 67.76 wt.% Fe, where wt.% is the mass percentage of each component relative to the total mass of the NdFeB magnet, and the diffusion source is 0.81 wt.% Tb and 0.02 wt.% Cu.
[0039] In one specific embodiment of the present invention, the diffusion matrix is composed of 29.6 wt.% Nd, 0.25 wt.% Cu, 0.15 wt.% Ti, 1 wt.% B, 0.06 wt.% Al and 68.03 wt.% Fe, where wt.% is the mass percentage of each component relative to the total mass of the NdFeB magnet, and the diffusion source is 0.65 wt.% Tb and 0.26 wt.% Cu.
[0040] In one specific embodiment of the present invention, the diffusion matrix is composed of 29.5 wt.% Nd, 0.8 wt.% Tb, 0.25 wt.% Cu, 0.15 wt.% Ti, 1 wt.% B, 0.06 wt.% Al and 67.12 wt.% Fe, where wt.% is the mass percentage of each component relative to the total mass of the NdFeB magnet, and the diffusion source is 0.85 wt.% Tb and 0.27 wt.% Cu.
[0041] In one specific embodiment of the present invention, the diffusion matrix is composed of 29.42 wt.% Nd, 0.25 wt.% Cu, 0.15 wt.% Ti, 1.01 wt.% B, 0.3 wt.% Al and 66.87 wt.% Fe, where wt.% is the mass percentage of each component relative to the total mass of the NdFeB magnet, and the diffusion source is 0.7 wt.% Tb and 0.3 wt.% Cu.
[0042] In one specific embodiment of the present invention, the diffusion matrix is composed of 22.28 wt.% Nd, 0.25 wt.% Cu, 0.15 wt.% Ti, 0.99 wt.% B, 0.06 wt.% Al and 67.91 wt.% Fe, where wt.% is the mass percentage of each component relative to the total mass of the NdFeB magnet, and the diffusion source is 0.65 wt.% Tb and 0.28 wt.% Cu.
[0043] In one specific embodiment of the present invention, the diffusion matrix is composed of 29.7 wt.% PrNd, 0.25 wt.% Cu, 0.15 wt.% Ti, 1 wt.% B, 0.06 wt.% Al and 67.9 wt.% Fe, where wt.% is the mass percentage of each component relative to the total mass of the NdFeB magnet, and the diffusion source is 0.66 wt.% Tb and 0.28 wt.% Cu.
[0044] The present invention further provides a method for producing the neodymium iron boron magnet, comprising the step of subjecting the diffusion substrate to grain boundary diffusion treatment with the diffusion source.
[0045] In the present invention, the grain boundary diffusion treatment may be carried out in a manner generally known in the art. In general, a diffusion source is formed on the surface of the diffusion substrate, followed by heat treatment.
[0046] In the present invention, the heat treatment temperature in the grain boundary diffusion treatment is preferably 850 to 950°C, more preferably 910 to 930°C, for example, 920°C.
[0047] In the present invention, the time for the heat treatment may be a time that is common in this field, and is preferably 10 to 40 hours, for example, 30 hours.
[0048] In the present invention, the method of forming the diffusion source is preferably magnetron sputtering, that is, forming a diffusion film layer on the surface of the diffusion substrate, for example, forming a Tb film layer or a Cu film layer first. As known to those skilled in the art, the method of using magnetron sputtering is simpler in process and less difficult to manufacture the diffusion source than the method of using TbCu alloy powder.
[0049] The present invention further provides a neodymium-iron-boron magnet produced by the above-mentioned method for producing a neodymium-iron-boron magnet.
[0050] The present invention further provides a neodymium iron boron magnet, the neodymium iron boron magnet comprising the following components: LR: 29 to 30.0 wt.%, the LR being a light rare earth element; Cu>0.5wt.%, B: 0.99-1.05 wt.%, Fe: 67.0-70.0 wt.%, where wt.% is the percentage of the mass of each component relative to the total mass of the neodymium iron boron magnet, The neodymium iron boron magnet further comprises Tb, The grain boundary phase of the neodymium iron boron magnet includes a Cu-rich phase having a width of 1 to 2.6 μm.
[0051] In the present invention, the grain boundary phase may have the meaning generally understood in the art, and is generally a general term for a region formed by a two-grain grain boundary phase and an intergranular triangular region. The two-grain grain boundary phase is generally a grain boundary phase between two main phase grains.
[0052] In the present invention, as known to those skilled in the art, the Cu-rich phase generally means a Cu-rich phase structure that can be intuitively seen in an EPMA analysis diagram, and the Cu content in the Cu-rich phase is 15 wt.% or more of the total mass of all elements in the region.
[0053] In the present invention, the width of the Cu-rich phase generally refers to the average value of the short side dimension of the Cu-rich region observed by EPMA, and the Cu-rich phase described in the present invention is generally irregular rod-shaped, i.e., the short side dimension is the average value of the width of the irregular long rod-shaped.
[0054] In the present invention, the width of the Cu-rich phase is preferably 1 to 2 μm, for example, 1.2 μm, 1.5 μm, 1.6 μm, 1.7 μm or 1.8 μm.
[0055] In the present invention, the LR content is preferably 29 to 29.5 wt.%, for example, 29.05 wt.%, 29.12 wt.%, 29.20 wt.%, 29.21 wt.%, 29.27 wt.%, 29.30 wt.%, 29.33 wt.%, 29.34 wt.% or 29.35 wt.%, where wt.% is the percentage of the total mass of the neodymium iron boron magnet.
[0056] In the present invention, the LR may be conventional in the art and may generally include one or more of Nd, Pr and PrNd alloys, preferably Nd, "Nd and Pr" or PrNd alloys.
[0057] When the LR is Nd, the Nd content is preferably 29 to 29.5 wt.%, for example, 29.05 wt.%, 29.12 wt.%, 29.20 wt.%, 29.21 wt.%, 29.27 wt.%, 29.30 wt.% or 29.34 wt.%, where wt.% is the percentage of the total mass of the neodymium iron boron magnet.
[0058] When the LR is Nd and Pr, the Nd content is preferably 21 to 23 wt.%, for example, 22 wt.%, and the Pr content is preferably 6 to 8 wt.%, for example, 7.35 wt.%, where wt.% is the percentage in the total mass of the neodymium iron boron magnet.
[0059] When the LR is a PrNd alloy, the content of the PrNd alloy is preferably 29 to 30 wt.%, for example, 29.33 wt.%, where wt.% is the percentage in the total mass of the neodymium iron boron magnet.
[0060] In the present invention, the Cu content is preferably 0.51 to 0.65 wt.%, for example, 0.51 wt.%, 0.52 wt.%, 0.53 wt.%, 0.55 wt.%, 0.61 wt.%, 0.62 wt.%, 0.63 wt.% or 0.65 wt.%, where wt.% is the percentage of the total mass of the neodymium iron boron magnet.
[0061] In the present invention, the B content is preferably 0.99 to 1.03 wt.%, for example 0.99 wt.%, 1 wt.%, or 1.01 wt.%, where wt.% is the percentage in the total mass of the neodymium iron boron magnet.
[0062] In the present invention, the Fe content is preferably 67.0 to 69 wt.%, for example, 67.33 wt.%, 67.88 wt.%, 67.94 wt.%, 68.06 wt.%, 68.04 wt.%, 68.26 wt.%, 68.27 wt.%, 67.48 wt.% or 68.52 wt.%, where wt.% is the percentage of the total mass of the neodymium iron boron magnet.
[0063] In the present invention, the Tb content is preferably 0.1 to 2 wt.%, for example, 0.65 wt.%, 0.66 wt.%, 0.7 wt.%, 0.81 wt.%, 0.85 wt.%, 0.86 wt.%, 0.88 wt.% or 1.65 wt.%, where wt.% is the percentage of the total mass of the neodymium iron boron magnet.
[0064] In the present invention, the neodymium iron boron magnet may further contain additive elements common in the art, such as one or more of Al, Co and Ti.
[0065] Here, when the neodymium iron boron magnet contains Al, the Al content may be 0.2 to 0.4 wt.%, for example, 0.3 wt.%, where wt.% is the percentage of the total mass of the neodymium iron boron magnet.
[0066] Here, when the neodymium iron boron magnet contains Co, the Co content may be 0.5 to 1.5 wt.%, for example, 1 wt.%, where wt.% is the percentage of the total mass of the neodymium iron boron magnet.
[0067] Here, when the neodymium iron boron magnet contains Ti, the Ti content may be 0.1 to 0.2 wt.%, for example, 0.15 wt.%, where wt.% is the percentage of the total mass of the neodymium iron boron magnet.
[0068] In the present invention, preferably, the NdFeB magnet does not contain Al and Co. As described above, not containing Al generally means that the Al content is 0.1 wt.% or less, for example, 0.06 wt.% or 0.07 wt.%, where wt.% is the percentage of the total mass of the NdFeB magnet.
[0069] In one specific embodiment of the present invention, the NdFeB magnet is composed of 29.34 wt.% Nd, 0.88 wt.% Tb, 0.62 wt.% Cu, 0.15 wt.% Ti, 1 wt.% B, 0.07 wt.% Al and 67.94 wt.% Fe, where wt.% is the percentage of the mass of each component relative to the total mass of the NdFeB magnet, and the grain boundary phase of the NdFeB magnet includes a Cu-rich phase having a width of 1.2 μm.
[0070] In one specific embodiment of the present invention, the NdFeB magnet is composed of 29.21 wt.% Nd, 0.86 wt.% Tb, 0.65 wt.% Cu, 0.15 wt.% Ti, 1 wt.% B, 0.07 wt.% Al and 68.06 wt.% Fe, where wt.% is the percentage of the mass of each component relative to the total mass of the NdFeB magnet, and the grain boundary phase of the NdFeB magnet includes a Cu-rich phase having a width of 1 μm.
[0071] In one specific embodiment of the present invention, the NdFeB magnet is composed of 29.27 wt.% Nd, 0.85 wt.% Tb, 0.63 wt.% Cu, 0.15 wt.% Ti, 0.99 wt.% B, 0.07 wt.% Al and 68.04 wt.% Fe, where wt.% is the percentage of the mass of each component relative to the total mass of the NdFeB magnet, and the grain boundary phase of the NdFeB magnet includes a Cu-rich phase having a width of 1.8 μm.
[0072] In one specific embodiment of the present invention, the NdFeB magnet is composed of 29.2 wt.% Nd, 0.81 wt.% Tb, 0.52 wt.% Cu, 0.15 wt.% Ti, 1 wt.% B, 0.06 wt.% Al and 68.26 wt.% Fe, where wt.% is the percentage of the mass of each component relative to the total mass of the NdFeB magnet, and the grain boundary phase of the NdFeB magnet includes a Cu-rich phase having a width of 2.5 μm.
[0073] In one specific embodiment of the present invention, the NdFeB magnet is composed of 29.12 wt.% Nd, 0.65 wt.% Tb, 0.51 wt.% Cu, 0.15 wt.% Ti, 0.99 wt.% B, 0.06 wt.% Al and 68.52 wt.% Fe, where wt.% is the percentage of the mass of each component relative to the total mass of the NdFeB magnet, and the grain boundary phase of the NdFeB magnet includes a Cu-rich phase having a width of 1.5 μm.
[0074] In one specific embodiment of the present invention, the NdFeB magnet is composed of 29.3 wt.% Nd, 1.65 wt.% Tb, 0.52 wt.% Cu, 0.15 wt.% Ti, 0.99 wt.% B, 0.06 wt.% Al and 67.33 wt.% Fe, where wt.% is the percentage of the mass of each component relative to the total mass of the NdFeB magnet, and the grain boundary phase of the NdFeB magnet includes a Cu-rich phase having a width of 1.5 μm.
[0075] In one specific embodiment of the present invention, the NdFeB magnet is composed of 29.05 wt.% Nd, 0.7 wt.% Tb, 0.55 wt.% Cu, 0.15 wt.% Ti, 1 wt.% Co, 1.01 wt.% B, 0.3 wt.% Al and 67.24 wt.% Fe, where wt.% is the percentage of the mass of each component relative to the total mass of the NdFeB magnet, and the grain boundary phase of the NdFeB magnet includes a Cu-rich phase having a width of 1.7 μm.
[0076] In one specific embodiment of the present invention, the NdFeB magnet is composed of 22 wt.% Nd, 7.35 wt.% Pr, 0.65 wt.% Tb, 0.53 wt.% Cu, 0.15 wt.% Ti, 0.99 wt.% B, 0.06 wt.% Al and 68.27 wt.% Fe, where wt.% is the percentage of the mass of each component with respect to the total mass of the NdFeB magnet, and the grain boundary phase of the NdFeB magnet includes a Cu-rich phase with a width of 1.6 μm.
[0077] In one specific embodiment of the present invention, the NdFeB magnet is composed of 29.33 wt.% PrNd, 0.66 wt.% Tb, 0.53 wt.% Cu, 0.15 wt.% Ti, 1 wt.% B, 0.06 wt.% Al and 68.27 wt.% Fe, where wt.% is the percentage of the mass of each component relative to the total mass of the NdFeB magnet, and the grain boundary phase of the NdFeB magnet includes a Cu-rich phase having a width of 1.5 μm.
[0078] The present invention further provides an application of said neodymium iron boron magnet as a material for manufacturing permanent magnet motors.
[0079] Here, the permanent magnet motor is, for example, an air conditioner compressor or a general-purpose servo motor.
[0080] By arbitrarily combining each of the above preferred conditions in accordance with the common knowledge in this field, each of the preferred embodiments of the present invention can be obtained.
[0081] All of the reagents and raw materials used in the present invention are commercially available. Effect of the Invention
[0082] The positive and progressive effect of the present invention is that the NdFeB magnet produced by the grain boundary diffusion material of NdFeB magnet can improve the coercive force significantly and maintain the residual magnetic flux density almost constant under the premise of adding the same content of heavy rare earth elements, so as to obtain a high-performance NdFeB magnet (for example, 54SH brand). [Brief description of the drawings]
[0083] [Figure 1] 1 is an EPMA analysis of the neodymium iron boron magnet in Example 4. [Diagram 2] 1 is an EPMA analysis of the neodymium iron boron magnet in Example 5. [Diagram 3] 1 is an EPMA analysis of the neodymium iron boron magnet in Example 7. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0084] The present invention will be further described below by way of examples, but the present invention is not limited to the scope of the above examples. In the following examples, the experimental methods for which no specific conditions are specified are selected according to the usual methods and conditions or according to the product specifications. Example 1 (1) Preparation of the diffusion matrix
[0085] According to the compounding method shown in Table 1, each component raw material is mixed, melted and refined in an induction furnace at a temperature condition of 1500±20℃, and then produced into a sheet-shaped alloy with a thickness of 0.3±0.05mm by high-speed quenching and melt spinning, which is then crushed into powder of 3-5μm by hydrogen crushing and jet mill crushing, molded under a magnetic field condition of 1.6T magnetic field strength or more, and then sintered at 1000-1100℃ for 4-6h to obtain a lump-shaped neodymium iron boron permanent magnet. The lump-shaped neodymium iron boron permanent magnet is cut into a sheet-shaped substrate to perform grain boundary diffusion. (2) Grain boundary diffusion treatment
[0086] The grain boundary diffusion treatment is performed by magnetron sputtering plating followed by heat treatment to obtain a neodymium iron boron magnet. The weight of the film layer increased by magnetron sputtering is 1.26wt.% (this weight is the total mass of Tb and Cu in the diffusion source), and the heat treatment temperature during the grain boundary diffusion treatment is 920℃ and the time is 30h.
[0087] The blending methods of the diffusion substrates and the diffusion sources during the grain boundary diffusion treatment in Examples 1 to 9 and Comparative Example 1 are shown in the following Table 1. The manufacturing steps and process parameters in Examples 2 to 9 and Comparative Example 1 are the same as those in Example 1.
[0088] Table 1 JPEG0007600415000001.jpg127161 Note: The element contents of the diffusion matrix in Table 1 were measured using an inductively coupled plasma optical emission spectrometry (ICP-OES). PrNd alloy means that the mass ratio of Nd to Pr is 3:1.
[0089] Here, " / " indicates that the element is not included. In the diffusion matrix, the content of each component is the percentage of the mass of each component relative to the total mass of the NdFeB magnet. The total mass of the diffusion matrix does not include unavoidable impurities introduced during the manufacturing process, such as C, O, etc. However, 0.08 wt.% or less of Al in the diffusion matrix is introduced from non-Al raw materials. In the diffusion source, the mass contents of Tb and Cu are the percentages of the mass of Tb and Cu, respectively, relative to the total mass of the NdFeB magnet. Effect Example 1 1. Measurement of the components of the neodymium-iron-boron magnets produced in Examples 1 to 9 and Comparative Example 1
[0090] The measurements were performed using an inductively coupled plasma optical emission spectrometer (ICP-OES). The test results are shown in Table 2 below.
[0091] Table 2 (units are wt.%) JPEG0007600415000002.jpg128161 Note: The content of each component is the percentage of the mass of each component relative to the total mass of the NdFeB magnet. The detection showed that the Nd content in the NdFeB magnet was reduced, which is believed to be because the grain boundary diffusion treatment corresponds to a heat treatment process, and a small amount of rare earth in the diffusion matrix is volatilized. 2. Magnetic performance test
[0092] Under room temperature conditions of 20℃, the magnetic performance of the neodymium iron boron magnets was tested using a PFM pulsed BH demagnetization curve tester.
[0093] The magnetic performance test results at 20° C. for five products in the same lot of the neodymium iron boron magnet of Example 1 are shown in Table 3 below.
[0094] Table 3 JPEG0007600415000003.jpg85160
[0095] As can be seen from Table 3, the magnetic properties of the products of the same lot according to the present invention are uniform and have excellent stability.
[0096] The average magnetic performance values of Example 1 are shown in Table 4 below. The other Examples were tested using the same method, and the final average magnetic performance values are shown in Table 4 below.
[0097] Table 4 JPEG0007600415000004.jpg232161 Note: RTB magnets mean neodymium iron boron magnets.
[0098] As can be seen from the data in the above table, the method of the present invention, which adds a specific amount of Cu to the diffusion matrix and adds specific amounts of Tb and Cu during the grain boundary diffusion process to combine with the specific diffusion matrix of the present invention, improves the coercivity more significantly than the method of adding only Tb during grain boundary diffusion. During the research and development process, the inventors also tried adding all of Cu during grain boundary diffusion, but the improvement in coercivity was the same as Comparative Example 1 and did not reach the level of the present invention.
[0099] Furthermore, the present invention has found a NdFeB magnet with better magnetic performance based on the above method. For example, when compared with Examples 1 to 3, it can be seen that when the Cu content in the diffusion matrix is 0.16wt.% or 0.24wt.%, the improvement in coercivity reaches 10kOe or more compared with when the Cu content is 0.34wt.%. For example, in Example 7, in which Al and Co are additionally added, the improvement in coercivity is only 8.72kOe compared with the other Examples. 3. Microstructural features
[0100] The neodymium iron boron magnets of Examples 1 to 9 and Comparative Example 1 are manufactured on a metallographic surface, and secondary electrons and X-rays are generated by alternately acting electrons and patterns on the metallographic surface product using an electron probe, and the shape of the sample is observed by the secondary electron signal, and the wavelength and intensity of the X-rays are measured to perform qualitative and quantitative analysis of the elements in the sample. For the measurement of the width of the Cu-rich phase, the surface scanning by the electron probe is used, and the short side dimension of the grain boundary Cu-rich phase is calibrated and measured with the scale tool of the device itself. Figure 1 shows the EPMA analysis of the neodymium iron boron magnet in Example 4. Figure 2 shows the EPMA analysis of the neodymium iron boron magnet in Example 5. Figure 3 shows the EPMA analysis of the neodymium iron boron magnet in Example 7, where Al shows a colloidal dispersion distribution, and Co is distributed in large amounts at the grain boundaries. Specific test results are shown in Table 5 below.
[0101] [Table 5] Note: The width of the Cu-rich phase means the average value of the short side dimension of the Cu-rich region observed by EPMA. For example, if the Cu-rich region is rod-shaped, the average value of the short side dimension is the average value of the width of the rod.
[0102] Combining Table 5 with Table 1, it can be seen that the width of the grain boundary Cu-rich phase is positively correlated with the Cu content added to the base material.
[0103] From the comparison of the above experiments, it was found that the Cu added in Example 4 was distributed in large amounts at the grain boundaries and in small amounts within the main phase crystal grains. The inclusion of Cu in the grain boundaries made the grain boundaries coarse, and the coarse grain boundaries reduced the main phase occupancy rate, reducing the residual magnetic flux density, and the coarse grain boundaries reduced the effect of the heavy rare earth demagnetization coupling diffused to the substrate grain boundaries, reducing the effect of Tb diffused to the substrate, thereby reducing the improvement value of the coercive force. In addition, in Example 5, the total amount of Cu content added was the same, but a smaller amount of Cu was distributed at the grain boundaries, which was more advantageous for the continuity of the grain boundaries and improved the coercive force.
Claims
1. A grain boundary diffusion material for a neodymium iron boron magnet, comprising a diffusion substrate and a diffusion source which is a diffusion target raw material added during grain boundary diffusion treatment; The diffusion matrix comprises the following components: LR: 29 to 30 wt. %, the LR being a light rare earth element; Cu: 0.15 to 0.5wt. %, B: 0.99-1.05wt. %, The balance is Fe, and wt. % is the percentage of the mass of each component with respect to the total mass of the neodymium iron boron magnet; the diffusion source includes Cu and Tb; The percentage of the mass of Cu in the neodymium iron boron magnet relative to the total mass of the neodymium iron boron magnet is greater than 0.5 wt. %; A grain boundary diffusion material for neodymium iron boron magnets.
2. The diffusion substrate is a sintered body; and / or the content of the LR in the diffusion matrix is 29.4-30 wt. %, where wt. % is a percentage of the total mass of the NdFeB magnet; and / or the LR comprises one or more of Nd, Pr and a PrNd alloy; When the LR is Nd, the Nd content is 29.4 to 29.8 wt. %, where wt. % is a percentage of the total mass of the Nd-Fe-B magnet; When the LR is Nd and Pr, the Nd content is 21-23 wt. %, and the Pr content is 6-8 wt. %, where wt. % is a percentage of the total mass of the neodymium iron boron magnet; When the LR is a PrNd alloy, the content of the PrNd alloy is 29-30 wt. %, where wt. % is the percentage in the total mass of the NdFeB magnet, and the mass ratio of Nd to Pr in the PrNd alloy is 3:1; and / or, in the diffusion matrix, the Cu content is 0.15-0.35 wt. %, where wt. % is a percentage of the total mass of the NdFeB magnet; and / or, in the diffusion matrix, the content of B is 0.99 to 1.03 wt. %, where wt. % is a percentage of the total mass of the NdFeB magnet; and / or, in the diffusion matrix, the Fe content is 67-69 wt. %, where wt. % is the percentage of the total mass of the NdFeB magnet; and / or, in the diffusion source, the content of Tb is 0.1 to 1.5 wt. %, where wt. % is the ratio of the content of Tb to the total mass of the NdFeB magnet; and / or the percentage of the mass of the Cu in the NdFeB magnet relative to the total mass of the NdFeB magnet is 0.51 to 0.65 wt. %; and / or the diffusion matrix further comprises one or more of Al, Co, Ti and Tb; When the diffusion matrix contains Al, the content of Al is 0.2-0.4 wt. % or 0.1 wt. % or less, where wt. % is a percentage of the total mass of the NdFeB magnet; When the diffusion matrix contains Co, the Co content is 0.5 to 1.5 wt. %, where wt. % is a percentage of the total mass of the NdFeB magnet; Alternatively, the diffusion matrix does not contain Co, When the diffusion matrix contains Ti, the Ti content is 0.1-0.2 wt. %, where wt. % is a percentage of the total mass of the NdFeB magnet; When the diffusion matrix contains Tb, the content of Tb is 1 wt. % or less.
2. The grain boundary diffusion material for neodymium iron boron magnets according to claim 1.
3. The method for producing the diffusion substrate includes the steps of melting, smelting, crushing, molding, and sintering a raw material composition of the diffusion substrate in this order, Here, the temperature of the melting and smelting is 1400 to 1550°C, wherein the thickness of the alloy sheet obtained after the melting and smelting is 0.25 to 0.5 mm; Here, the pulverization is carried out in the order of hydrogen pulverization and jet mill pulverization, and the particle size of the powder obtained after the pulverization is 3 to 5 μm; Here, the molding is a magnetic field molding, and the magnetic field strength of the magnetic field molding is 1.6 T or more, wherein the sintering temperature is 1000 to 1100° C. Here, the sintering time is 4 to 6 h.
3. The grain boundary diffusion material for neodymium iron boron magnets according to claim 2.
4. The diffusion matrix is composed of 29.6 wt.% Nd, 0.24 wt.% Cu, 0.15 wt.% Ti, 1 wt.% B, 0.06 wt.% Al and 67.69 wt.% Fe, where wt.% is the percentage of the mass of each component relative to the total mass of the NdFeB magnet, and the diffusion source is 0.88 wt.% Tb and 0.38 wt.% Cu; Alternatively, the diffusion matrix is composed of 29.68 wt.% Nd, 0.16 wt.% Cu, 0.15 wt.% Ti, 1 wt.% B, 0.06 wt.% Al and 67.6 wt.% Fe, where wt.% is the percentage of the mass of each component relative to the total mass of the NdFeB magnet, and the diffusion source is 0.86 wt.% Tb and 0.49 wt.% Cu; Alternatively, the diffusion matrix is composed of 29.73 wt.% Nd, 0.34 wt.% Cu, 0.15 wt.% Ti, 1 wt.% B, 0.07 wt.% Al and 67.57 wt.% Fe, where wt.% is the percentage of the mass of each component relative to the total mass of the NdFeB magnet, and the diffusion source is 0.85 wt.% Tb and 0.29 wt.% Cu; Alternatively, the diffusion matrix is composed of 29.7 wt.% Nd, 0.5 wt.% Cu, 0.15 wt.% Ti, 1 wt.% B, 0.06 wt.% Al and 67.76 wt.% Fe, where wt.% is the percentage of the mass of each component relative to the total mass of the NdFeB magnet, and the diffusion source is 0.81 wt.% Tb and 0.02 wt.% Cu; Alternatively, the diffusion matrix is composed of 29.6 wt.% Nd, 0.25 wt.% Cu, 0.15 wt.% Ti, 1 wt.% B, 0.06 wt.% Al and 68.03 wt.% Fe, where wt.% is the percentage of the mass of each component relative to the total mass of the NdFeB magnet, and the diffusion source is 0.65 wt.% Tb and 0.26 wt.% Cu; Alternatively, the diffusion matrix is composed of 29.5 wt. % Nd, 0.8 wt. % Tb, 0.25 wt. % Cu, 0.15 wt. % Ti, 1 wt. % B, 0.06 wt. % Al and 67.12 wt. % Fe, where wt. % is the percentage of the mass of each component relative to the total mass of the NdFeB magnet, and the diffusion source is 0.85 wt. % Tb and 0.27 wt. % Cu; Alternatively, the diffusion matrix is composed of 29.42 wt.% Nd, 0.25 wt.% Cu, 0.15 wt.% Ti, 1.01 wt.% B, 0.3 wt.% Al and 66.87 wt.% Fe, where wt.% is the percentage of the mass of each component relative to the total mass of the NdFeB magnet, and the diffusion source is 0.7 wt.% Tb and 0.3 wt.% Cu; Alternatively, the diffusion matrix is composed of 22.28 wt.% Nd, 0.25 wt.% Cu, 0.15 wt.% Ti, 0.99 wt.% B, 0.06 wt.% Al and 67.91 wt.% Fe, where wt.% is the percentage of the mass of each component relative to the total mass of the NdFeB magnet, and the diffusion source is 0.65 wt.% Tb and 0.28 wt.% Cu; Alternatively, the diffusion matrix is composed of 29.7 wt.% PrNd, 0.25 wt.% Cu, 0.15 wt.% Ti, 1 wt.% B, 0.06 wt.% Al and 67.9 wt.% Fe, where wt.% is the percentage of the mass of each component relative to the total mass of the neodymium iron boron magnet, and the diffusion source is 0.66 wt.% Tb and 0.28 wt.% Cu; 4. The grain boundary diffusion material of neodymium iron boron magnet according to claim 3.
5. A method for producing a neodymium iron boron magnet, comprising the steps of: subjecting a diffusion substrate according to any one of claims 1 to 4 to a grain boundary diffusion treatment using a diffusion source according to any one of claims 1 to 4; Here, in the grain boundary diffusion treatment, the heat treatment temperature is 850 to 950° C., Here, in the grain boundary diffusion treatment, the heat treatment time is 10 to 40 hours, Wherein, the diffusion source is formed by magnetron sputtering. A method for producing a neodymium iron boron magnet.
6. Produced by the method for producing a neodymium iron boron magnet according to claim 5. A neodymium iron boron magnet characterized by:
7. A neodymium iron boron magnet comprising: LR: 29 to 30.0 wt. %, the LR being a light rare earth element; Cu>0.5wt. %, B: 0.99-1.05wt. %, The balance is Fe, and wt. % is the percentage of the mass of each component with respect to the total mass of the neodymium iron boron magnet; The neodymium iron boron magnet further comprises Tb, The grain boundary phase of the neodymium iron boron magnet includes a Cu-rich phase having a width of 1 to 2.6 μm. A neodymium iron boron magnet characterized by:
8. The percentage of the mass of Cu in the Cu-rich phase relative to the total mass of all elements in the Cu-rich phase is 15 wt. % or more; and / or the width of the Cu-rich phase is 1 to 2 μm; and / or the LR content is 29-29.5 wt. %, where wt. % is a percentage of the total mass of the NdFeB magnet; and / or the LR comprises one or more of Nd, Pr and a PrNd alloy; When the LR is Nd, the content of the Nd is 29 to 29.5 wt. %, where wt. % is a percentage of the total mass of the Nd-Fe-B magnet; When the LR is Nd and Pr, the Nd content is 21-23 wt. %, and the Pr content is 6-8 wt. %, where wt. % is a percentage of the total mass of the neodymium iron boron magnet; When the LR is a PrNd alloy, the content of the PrNd alloy is 29-30 wt. %, where wt. % is the percentage in the total mass of the NdFeB magnet; and / or the Cu content is 0.51 to 0.65 wt. %, where wt. % refers to the percentage in the total mass of the NdFeB magnet; and / or the content of B is 0.99 to 1.03 wt. %, where wt. % is a percentage of the total mass of the neodymium iron boron magnet; and / or the Fe content is 67.0 to 69 wt. %, where wt. % is a percentage of the total mass of the neodymium iron boron magnet; and / or the content of Tb is 0.1 to 2 wt. %, where wt. % is a percentage of the total mass of the neodymium iron boron magnet; and / or the neodymium iron boron magnet further comprises one or more of Al, Co and Ti; When the neodymium iron boron magnet contains Al, the content of Al is 0.2 to 0.4 wt. % or 0.1 wt. % or less, where wt. % is a percentage of the total mass of the neodymium iron boron magnet; When the neodymium iron boron magnet contains Co, the content of Co is 0.5 to 1.5 wt. %, where wt. % is a percentage of the total mass of the neodymium iron boron magnet; Alternatively, the neodymium iron boron magnet does not contain Co, When the neodymium iron boron magnet contains Ti, the content of Ti is 0.1 to 0.2 wt. %, where wt. % is a percentage of the total mass of the neodymium iron boron magnet.
8. The neodymium iron boron magnet according to claim 7.
9. The neodymium iron boron magnet is composed of 29.34 wt. % Nd, 0.88 wt. % Tb, 0.62 wt. % Cu, 0.15 wt. % Ti, 1 wt. % B, 0.07 wt. % Al, and 67.94 wt. % Fe, where wt. % is the percentage of the mass of each component relative to the total mass of the neodymium iron boron magnet, and the grain boundary phase of the neodymium iron boron magnet includes a Cu-rich phase having a width of 1.2 μm, Alternatively, the neodymium iron boron magnet is composed of 29.21 wt. % Nd, 0.86 wt. % Tb, 0.65 wt. % Cu, 0.15 wt. % Ti, 1 wt. % B, 0.07 wt. % Al and 68.06 wt. % Fe, where wt. % is the percentage of the mass of each component with respect to the total mass of the neodymium iron boron magnet, and the grain boundary phase of the neodymium iron boron magnet includes a Cu-rich phase having a width of 1 μm, Alternatively, the neodymium iron boron magnet is composed of 29.27 wt. % Nd, 0.85 wt. % Tb, 0.63 wt. % Cu, 0.15 wt. % Ti, 0.99 wt. % B, 0.07 wt. % Al and 68.04 wt. % Fe, where wt. % is the percentage of the mass of each component with respect to the total mass of the neodymium iron boron magnet, and the grain boundary phase of the neodymium iron boron magnet includes a Cu-rich phase having a width of 1.8 μm; Alternatively, the neodymium iron boron magnet is composed of 29.2 wt. % Nd, 0.81 wt. % Tb, 0.52 wt. % Cu, 0.15 wt. % Ti, 1 wt. % B, 0.06 wt. % Al and 68.26 wt. % Fe, where wt. % is the percentage of the mass of each component with respect to the total mass of the neodymium iron boron magnet, and the grain boundary phase of the neodymium iron boron magnet includes a Cu-rich phase having a width of 2.5 μm; Alternatively, the neodymium iron boron magnet is composed of 29.12 wt. % Nd, 0.65 wt. % Tb, 0.51 wt. % Cu, 0.15 wt. % Ti, 0.99 wt. % B, 0.06 wt. % Al and 68.52 wt. % Fe, where wt. % is the percentage of the mass of each component with respect to the total mass of the neodymium iron boron magnet, and the grain boundary phase of the neodymium iron boron magnet includes a Cu-rich phase having a width of 1.5 μm; Alternatively, the neodymium iron boron magnet is composed of 29.3 wt. % Nd, 1.65 wt. % Tb, 0.52 wt. % Cu, 0.15 wt. % Ti, 0.99 wt. % B, 0.06 wt. % Al and 67.33 wt. % Fe, where wt. % is the percentage of the mass of each component with respect to the total mass of the neodymium iron boron magnet, and the grain boundary phase of the neodymium iron boron magnet includes a Cu-rich phase having a width of 1.5 μm; Alternatively, the neodymium iron boron magnet is composed of 29.05 wt. % Nd, 0.7 wt. % Tb, 0.55 wt. % Cu, 0.15 wt. % Ti, 1 wt. % Co, 1.01 wt. % B, 0.3 wt. % Al and 67.24 wt. % Fe, where wt. % is the percentage of the mass of each component with respect to the total mass of the neodymium iron boron magnet, and the grain boundary phase of the neodymium iron boron magnet includes a Cu-rich phase having a width of 1.7 μm; Alternatively, the neodymium iron boron magnet is composed of 22 wt. % Nd, 7.35 wt. % Pr, 0.65 wt. % Tb, 0.53 wt. % Cu, 0.15 wt. % Ti, 0.99 wt. % B, 0.06 wt. % Al and 68.27 wt. % Fe, where wt. % is the percentage of the mass of each component with respect to the total mass of the neodymium iron boron magnet, and the grain boundary phase of the neodymium iron boron magnet includes a Cu-rich phase having a width of 1.6 μm; Alternatively, the neodymium iron boron magnet is composed of 29.33 wt. % PrNd, 0.66 wt. % Tb, 0.53 wt. % Cu, 0.15 wt. % Ti, 1 wt. % B, 0.06 wt. % Al and 68.27 wt. % Fe, where wt. % is the percentage of the mass of each component relative to the total mass of the neodymium iron boron magnet, and the grain boundary phase of the neodymium iron boron magnet includes a Cu-rich phase having a width of 1.5 μm.
9. The neodymium iron boron magnet according to claim 8.
Citation Information
Patent Citations
Neodymium-iron-boron magnet material, raw material composition, preparation method and application
CN111223625A
R-t-b based permanent magnet
JP2021158342A
